The story of philosophy - Durant, Will, 1885-1981 (Garden City, New York : Dover Publications, 2022)
"Pulitzer Prize-winning author Will Durant chronicles the lives and ideas of key philosophers throughout history in this informative yet eminently readable text. Beginning with Socrates and Plato and concluding with Friedrich Nietzsche, Durant builds a history of philosophy by showing how each thinker's ideas informed and influenced the next generation"--
"Pulitzer Prize-winning author Will Durant chronicles the lives and ideas of several key philosophical thinkers throughout history in this informative yet eminently readable text. Beginning with Socrates and Plato and concluding with Friedrich Nietzsche, with twelve other prominent philosophers between them, the author builds a history of philosophy by showing how each thinker's ideas informed and influenced the next generation. An essential read for anyone fascinated by the development of Western philosophy"--
Includes bibliographical references (pages 483-484).
Keywords: Philosophy -- History; Philosophers; PHILOSOPHY / History & Surveys / General